The Europe 2020 project bond initiative: an alternative to finance infrastructure in Europe - Vassallo, José Manuel; Rangel, Thais; Baeza, María de los Ángeles; Bueno, Paola Carolina (Technological and Economic Development of Economy, 2018)
The economic and financial crisis that struck Europe over the last few years has imposed much stricter capital and liquidity requirements for commercial banks thereby reducing their ability to provide funding to infrastructure projects. To circumvent this problem the European Union has promoted the Europe 2020 Project Bond Initiative (PBI) aimed at using European funds for credit enhancement to increase the appetite of institutional investors – such as pension funds and insurance companies – to boost large-scale infrastructure financing. In this paper we describe the specific constraints and attractiveness of the PBI within Europe using the SWOT methodology to analyse the information coming from both pilot case studies and the responses that institutional investors and other stakeholders provided to the EC public consultation about the PBI. On the basis of this information we found that even though the initiative may contribute to facilitate infrastructure financing in Europe, there are still some challenges to be addressed for its right implementation.First published online 9 January 2017